Faktor-faktor yang Mempengaruhi Publikasi Informasi Keuangan pada Website Resmi Pemerintah Daerah se-Jawa Tengah - Eva Anggara Yunita (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2021)
This study aims to find out which factors have strong impact to the financial report publications on local government websites, due to the requirements of Good Government Governance, among others the principle of transparency and accountability. District/city governments in Central Java were selected as samples by consideration of the achievements and awards achieved related to transparency, accountability, and compliance. The variables used in this study were political competition, tenure, BPK audit options, total assets, leverage, and direct expenditure. Using Stata probit regression analysis tool, the results showed that the local governments in Central Java were in the increase of transparency and accountability stage, where this showed the success of the regional autonomy mission. There were upward trend of audit opinions and financial report publications on local government websites. All variables insufficiently affected internet publication of financial report The political map did not become disincentive for local heads in order to increase the transparency of financial reporting.